Socialization and Wellness Tourism Training to Encourage Self-sufficient Educational Tourism in the Sumber Manis Nature Tourism, Banyuwangi - Danang Ari Santoso; Adi Mulyadi; Moh. Agung Setiabudi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2026)
This paper discusses the socialization and training of wellness tourism for the Gombengsari Tourism Awareness Group. The Gombengsari Tourism Awareness Group has management and marketing problems in managing tourism. This is due to a lack of knowledge in mapping and managing tourism concepts. Therefore, socialization and training were carried out to improve the management and marketing of tourist destinations. The socialization and training include the application of wellness tourism spot technology, mentoring, evaluation, and program sustainability. The results of the socialization and training show that mapping has been carried out on wellness tourism spots and flying fox spots. Tourism destination marketing is carried out once every two weeks in managing financial management and partner businesses. Website-based promotion and inter-regional tourism destination marketing training are also conducted. Website-based tourism destination promotion has increased tourist visitors by ±50-75% in one month.